Pollution Index of Cileungsi-Cikeas-Bekasi River. Issue 1 (April 2021) - Effendi, H; Prayoga, G; Azhar, A R; Permadi, T; Santoso, E N
Abstract: Water quality data of the Cileungsi-Cikeas-Bekasi River (survey results and monitoring data) were analyzed using the Pollution Index (IP) according to the calculation guidelines listed in the Ministry of Environment Decree No. 115 of 2003 concerning Guidelines for Determining Water Quality Status. The goal was to determine the status of the quality or level of river water pollution. The quality standard used in the calculation refers to the class II quality standard based on the West Java Governor Regulation No. 12 of 2013 concerning Water Quality Standards and Water Pollution Control in Cimanuk River, Cilamaya River, and Bekasi River. The PI value of the Cileungsi River shows that the quality status of the Cileungsi River was in moderate pollution, except in the upstream part (good condition). Status of Cikeas River water quality was still in good condition, except in the downstream segment (light pollution). Based on data from the 2019 survey and monitoring of Environmental Agency (DLH) of Bekasi City in the second semester of 2018, the water quality status of Bekasi River is moderate pollution in all segments.